O Percurso de um analista: A Presença do analista do corpo ao espírito - Lourenção, Ricardo Tadeu Torres (2006)
This dissertation intend explorer another versant of analitic relationship that transcend the ambit of transference. The analitic setting can and need to admit another facets of human person like: the corporeity, the community and the spirituality. Thus it´s necessary that the analist place himself in a personal way in relationship, that I named it presence. The analist acting as long as presence justify himself like a transpose trial the compartmented vision and technicist, that impose itself in the context of the pos-modern world we live. And it s one of the principal generating causes of the contemporary sufferings. Through of the clinic I propose myself to explorer these versants, specialy the spiritual one, that in my point of view enfold every ones, and its little exploreds, although always present. I employed as access instrument to this versant, my acumulated practice Aikidô experience